Genetic loss of susceptibility: a costly route to disease resistance?. (6th August 2013) - Hückelhoven, R.; Eichmann, R.; Weis, C.; Hoefle, C.; Proels, R. K.
Abstract : The susceptibility of plants to microbial pathogens involves molecular interactions between microbial effectors and host targets. In most cases, pathogen effectors prevent recognition or suppress host defence. However, successful suppression of host defence is not always sufficient for pathogenesis, which requires further host components that meet the demands of pathogen development and nutrition. Additionally, the plants possess negative regulators of immune response to avoid autoimmunity and unnecessary investment into defence in environments with little disease pressure. Consequently, disease susceptibility can be lost by mutation of negative regulators of defence, but also of other host factors that otherwise support the successful pathogen. Here, genetic loss of susceptibility to adapted microbial pathogens is reviewed, with a focus on examples of lost susceptibility to powdery mildew. Costs of resistance and potential consequences for application in breeding and biotechnology are discussed.